Identifying the psyching-up strategies used in strength sports: a concept mapping approach - Cusimano, K.; Freeman, D. P.; Moran, D. J. (The Journal of Strength and Conditioning Research, 2025)
It has frequently been reported that strength athletes use psyching-up strategies to enhance performance. Despite numerous investigations into the efficacy of these psyching-up strategies, there has yet to be a thorough exploration of the methods used by athletes to do so. Thus, it is important to explore the full breadth of strategies used by athletes. This study aimed to identify the psyching-up strategies used by strength sport athletes and assess the perceived effectiveness on performance. Using a concept mapping approach, 246 strength sport athletes and coaches participated in an initial statement (technique) generation phase, and 112 sorted the techniques into clusters and rated the effectiveness of each technique at enhancing maximal strength performance. In the generation stage, 64 individual psyching-up techniques were identified. Similarity matrix generation, multidimensional scaling, and hierarchical cluster analysis were used to produce visual cluster maps, which identified 8 separate clusters of psyching-up strategies: "pre-performance routines"; "positive thoughts, feelings, images, and behaviors"; "goals and performance accomplishments"; "self-deprecation"; "negative thoughts, feelings, images, and behaviors"; "stimulation"; "physical and physiological techniques"; and "aggressive acts". Participants ranked "pre-performance routines" as being the most effective psyching-up strategy, with males reporting significantly higher ratings for "self-deprecation"; "negative thoughts, feelings, images, and behaviors"; "stimulation"; and "aggressive acts". The present findings demonstrated a greater breadth of psyching-up techniques than those currently examined within the literature. Accordingly, we suggest a revised definition of psyching-up strategies in the context of strength sports: "strategies intending to alter activation or to enhance mental preparedness, immediately prior to or during skill execution".